Formas de expressão e recuperação do vigor de Lagerstroemia indica L. após adubação em diferentes tipologias da floresta urbana de Irati-PR - Ivasko Júnior, Severo (2018)
The negative effects of urbanization over urban trees claims the search for alternatives to control damages in order to maintain the benefits provided by them. The present study aimed to characterize different forms of expression and recovery of vigor of Lagerstroemia indica L. in an urban park, in a public square, and in the sidewalks of streetscape composition in the city of Irati-PR. For this, two field experiments were evaluated. After measurements of vegetative, physiological, and flowering vigor of trees in the growing season of 2016, liming was applied in the soil. The experiment 1 tested the elevation of nitrogen, phosphorus, and potassium contents in a 100% base in relation to the soil content observed in the soil analysis interpretation from the urban park and the from sidewalks. The experiment 2 tested increasing phosphorus dosages at 50, 100, 150 and 200% of the initial soil content over trees in the public square. In the growing season of 2017, a remeasure of vigor was carried out aiming to evaluate the effect of the fertilization applied. Data from experiment 1 were analyzed by means of Wilcoxon and Friedman tests, while data from experiment 2 data were analyzed by means of Kruskal-Wallis test. It was observed that for length of the branch, average distance internodes, leaf area, width and length of flowering, treatments with potassium and phosphate fertilization, in experiment 1, and the higher dosage of phosphate fertilization (200%), in experiment 2, provided the highest mean values. The variables dark green color and chlorophyll a and b were not affected by the treatments given in both experiments. It is concluded that the vegetative and flowering vigor was significantly affected by fertilization, while the physiological vigor was not responsive to fertilizer application. Therefore, in experiment 1, fertilization with 351 mg/dm³ of K+ and 12 mg/dm³ of P in soil, and in experiment 2, the application of 10 mg/dm³ of P, provided the highest expressions of vigor in Lagerstroemia indica L.